UANG PANAI’: MENYOROTI PERGESERAN PARADIGMA MASYARAKAT KONTEMPORER PERSPEKTIF HUKUM ISLAM - Nurfadillah, Rizkyanti; Putri Ayu Ramadhani; Al Fitrah Maharanny (IAIN Parepare, 2024)
The Panai’ money tradition in Indonesia has experienced a shift in meaning and practice in the contemporary era. The increase in its value triggers financial burdens, delays in marriage, disputes between families, and exploitation of women. The phenomenon of